Vascular inflammation in chronic kidney disease: the role of uremic toxins in macrophage activation - Jha, Prabhash Kumar; Nakano, Toshiaki; Itto, Lucas Yuji Umesaki; Barbeiro, Miguel Cantadori; Lupieri, Adrien; Aikawa, Elena; Aikawa, Masanori (Frontiers in Cardiovascular Medicine, 2025)
Chronic kidney disease (CKD) is a progressive condition characterized by the gradual loss of kidney function, leading to the accumulation of uremic toxins in the bloodstream. These toxins play a pivotal role in mediating vascular inflammation, a key contributor to the high cardiovascular morbidity and mortality observed in CKD patients. This review article explores the intricate mechanisms by which uremic toxins accelerate vascular inflammation. Macrophages, as versatile immune cells, are central to the inflammatory response. Evidence suggests that the uremic milieu influences macrophage biology. In this review article, we focus on the signaling through which uremic toxins, particularly indoxyl sulfate—an independent risk factor for cardiovascular complications in CKD patients, modulate macrophage activation and function, and how these changes contribute to vascular inflammation, leading to the increased cardiovascular risk. Investigation of such mechanisms provide molecular bases for the development of new therapies that retard the development of cardiovascular disorders in CKD patients.